The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1115/1.4044401
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Enabled Multi-Fidelity Platform for the Integrated Design of Aircraft Systems

Abstract: The push toward reducing the aircraft development cycle time motivates the development of collaborative frameworks that enable the more integrated design of aircraft and their systems. The ModellIng and Simulation tools for Systems IntegratiON on Aircraft (MISSION) project aims to develop an integrated modelling and simulation framework. This paper focuses on some recent advancements in the MISSION project and presents a design framework that combines a filtering process to down-select feasible architectures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The optimization procedure employs a data-driven localization stage to recognize files with comparable structures. The framework displays the capacity to optimize across numerous system architectures in a manner that is efficient and scalable for bigger design spaces and problems of greater sizes [82].…”
Section: Platform For Integrated Aircraft Designmentioning
confidence: 99%
“…The optimization procedure employs a data-driven localization stage to recognize files with comparable structures. The framework displays the capacity to optimize across numerous system architectures in a manner that is efficient and scalable for bigger design spaces and problems of greater sizes [82].…”
Section: Platform For Integrated Aircraft Designmentioning
confidence: 99%
“…For a low-dimensional interpretable space (for example the flight conditions), the physical region could be defined by flight mechanics specialists [316], but it is intractable to manually determine the desired regions for high-dimensional geometric design space. Design space filtering has been proposed in ASO as an efficient way to exclude the abnormal regions, and similar attempts have been applied in other design problems [317,318]. This approach does not reduce the number of design variables; instead, it shrinks the design space by defining a constraint function to evaluate the abnormality of samples.…”
Section: Geometric Filteringmentioning
confidence: 99%
“…Chakraborty and Mavris introduce heuristics-based checks to ensure that system architectures are defined correctly to provide meaningful results when evaluated by their integrated systems sizing and performance estimation framework [46]. Recent work by Garriga et al [47] has demonstrated the use of configurational filters in determining the feasibility of a large design space of landing gear braking and flight control system architectures. Using configurational rules and heuristics to test if system architectures are feasible (at least from a configurational point of view) can also be extended to incorporate some safety aspects.…”
Section: Safety Aspects Included In System Architecture Definitionmentioning
confidence: 99%